Experimental Evaluation of Optimal Rate Delay and Power Allocation Algorithm in Wireless Control Networks - Muhammad Tahir; S. K. Mazumder (Journal of Electrical and Computer Engineering)
The network utility maximization (NUM) framework, widely used for wireless networks to achieve optimal resource allocation, has led to both centralized as well as distributed algorithms. We compare the convergence performance of centralized realization of the NUM framework with that of distributed realization by implementing the algorithms using a hardware test-bed. Experimental results show a superior convergence performance for centralized implementation compared to the distributed implementation, which is attributed to the dominance of communication delay over processing delay. The convergence results for the distributed case also show a tradeoff between processing time and the associated communication overhead providing an optimal termination criterion for the convergence of different subproblems.